The Influence Of E-Hrm On Organizational Performance With Mediation Of Employee Performance And Job Satisfaction Indonesia Multiple Companies - Helen Caroline; Setia Tjahyanti (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2025)
e-HRM is an important strategy for companies to improve organizational performance. The purpose of this study is to examine how e-HRM affects organizational performance through mediation of job satisfaction and employee performance in several companies in Indonesia. This study uses quantitative methods, the sample selection in this study is non probability sampling using purposive sampling technique by collecting data through online questionnaires via google form distributed to respondents. The population of this study consisted of certain time work agreement employees with more than one year of service in several companies in Indonesia. The data analysis method used in this research is the Structural Equation Model (SEM) data analysis method using SmartPLS4 software. Empirical evidence that the implementation of an effective e-HRM system can improve organizational performance through improved employee performance and job satisfaction is provided by research findings showing that employee performance and job satisfaction act as mediators that strengthen the relationship between e-HRM and organizational performance.